Unpacking Staffing Struggles: How ABC Sdn. Bhd. Can Overcome Employee Retention Challenges in Manufacturing - Ismail, Nurul Ain Natasha; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2024)
ABC Sdn Bhd encompasses distribution and retail divisions, which are involved in assembling, producing, and distributing a wide range of automotive components and accessories for both domestic and international markets. One of the challenges faced by the company in its manufacturing department is the lack of sufficient staffing and employee retention. This study aims to examine the current practices for maintaining staffing and employee retention and to explore the challenges associated with minimal staffing and employee retention in this sector. A qualitative approach, including interviews and purposive sampling of selected human resources at ABC Sdn Bhd, was utilized for this study. The thematic analysis method was employed to identify patterns, themes, and categories within the data, providing a comprehensive understanding of the study topic. This study explored human resource management’s facts, knowledge, and perceptions through structured interviews. The findings offer valuable insights into the current practices for maintaining staffing and employee retention, helping ABC Sdn Bhd pinpoint areas for improvement and refine their human resource management strategies. Identifying best practices, key factors, and challenges is crucial for developing effective workflows and achieving business goals.